Assortative interactions and leadership in a free-ranging population of juvenile lemon shark Negaprion brevirostris - Guttridge, T.; Gruber, S.; Di Battista, Joseph; Feldheim, K.; Croft, D.; Krause, S.; Krause, J. (Inter-Research, 2011)
For marine predators there is a paucity of studies on social behaviour, and even fewer studies have quantified interactions between individuals. In the present study, we looked at the social structure and leadership of free-ranging juvenile lemon shark Negaprion brevirostris in a known aggregation site, Bimini, the Bahamas. Observations of these sharks were made from towers placed in a mangrove inlet, where clear, shallow, protected waters made it possible to record group compositions of externally colour-code tagged wild juvenile lemon sharks. Thirty-eight different individual sharks were observed to use the area over a 2 yr period. Results show repeated social interactions suggestive of active partner preference. In addition, we found that group structure was mostly explained by body length, and possibly by preference for relatives but not by sex. Finally, we observed that some sharks led more groups than others and that those lead individuals were usually larger than those following them. This study quantifies the social structure of a free-ranging shark population and provides novel insights into the social behaviour of juvenile sharks. © Inter-Research 2011.